How semantics works in Chinese relative clause processing: insights from eye tracking - Liu, Yan; Ni, Chuanbin (Frontiers in Psychology, 2024)
Recent years have witnessed much research on semantic analysis and syntactic anatomy in ordinary language processing. However, it is still a matter of considerable debate about when and how the semantic integration of single word meanings works and interacts with syntax during on-line comprehension. This study, in an eye-tracking paradigm, took 38 native speakers of Mandarin Chinese as the participants and took Chinese relative clauses as stimuli to figure out the functions of semantics by investigating the conditioning semantic factors influencing and governing the word order variation of Chinese relative clauses during different processing stages. Accordingly, this study manipulated two syntactic variables, i.e., relative clause type and the position of the numeral-classifier sequence (NCL) in the relative clause, as well as a semantic variable, i.e., the abstractness of the head noun that the relative clause modified. Specifically, the study addressed two questions: (1) when semantics is activated and interacts with syntax and (2) how semantics affects syntax during the time course of Chinese relative clause processing. The results indicated that: (1) Semantics was activated and interacted with syntax during the early and late processing stages of Chinese relative clauses, which challenged the sequential order of syntactic and semantic processes, and supported the claims of the Concurrent Processing Model. (2) The syntactic order of the Chinese relative clause was affected by the semantic information of the head noun that the clause modified. Object-extraction relative clauses (ORCs) had a conjunction preference for the order “an object relative clause preceding the numeral-classifier sequence and the head noun.” Instead, the subject-extraction relative clause (SRC) which modified a concrete noun (CN) had a co-occurrence preference for the order “numeral-classifier sequence preceding the subject relative clause and the head noun,” while the subject-extraction relative clause which modified an abstract noun (AN) had a co-occurrence preference for the order “subject relative clause preceding the numeral-classifier sequence and the head noun.” The findings of this study were evaluated in light of the perspectives of truth value semantics of the syntactic components, the semantic compatibility of numeral-classifier sequence and its modified noun as well as the discourse functions of outer modifier nominals and inner modifier nominals.